2017
DOI: 10.1089/neu.2016.4516
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stand and Step Training with Epidural Stimulation on Motor Function for Standing in Chronic Complete Paraplegics

Abstract: Individuals affected by motor complete spinal cord injury are unable to stand, walk, or move their lower limbs voluntarily; this diagnosis normally implies severe limitations for functional recovery. We have recently shown that the appropriate selection of epidural stimulation parameters was critical to promoting full-body, weight-bearing standing with independent knee extension in four individuals with chronic clinically complete paralysis. In the current study, we examined the effects of stand training and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 59 publications
2
83
0
2
Order By: Relevance
“…Stand training with EES improved standing ability in all four individuals tested. However, step training without stand training decreased EES‐enabled standing ability . Furthermore, one subject regained the ability to stand with independent knee and hip extension without EES following 3.7 years of activity‐based training with EES .…”
Section: Evidence Of Intentional Control Over Ees‐enabled Motor Functmentioning
confidence: 95%
See 1 more Smart Citation
“…Stand training with EES improved standing ability in all four individuals tested. However, step training without stand training decreased EES‐enabled standing ability . Furthermore, one subject regained the ability to stand with independent knee and hip extension without EES following 3.7 years of activity‐based training with EES .…”
Section: Evidence Of Intentional Control Over Ees‐enabled Motor Functmentioning
confidence: 95%
“…The importance of rehabilitation in recovering stepping ability has been shown to be critical in both animal models and humans following SCI. To date, all reported subjects using EES for motor recovery following paraplegia have achieved the results following months of motor training prior to implant of the device to demonstrate lack of recovery with motor training without EES followed by EES in combination with motor training . Therefore, it is difficult to separate the variables of how much the motor training and stimulation, respectively, are contributing to restoration of function.…”
Section: Limitations Of Eesmentioning
confidence: 99%
“…[125][126][127][128][129][130] This approach takes advantage of sophisticated spinal networks below the level of injury to unexpectedly reactivate spared pathways, restoring supraspinal connectivity and resulting in functional recovery in those initially diagnosed clinically as motor complete. [126][127][128][129][130][131][132] During the course of some of these initial studies to restore stepping and standing using lumbosacral scES in motor complete humans, investigators discovered that individuals with cardiovascular dysfunction showed increases in SBP with stimulation. [133][134][135] This response also allowed upright standing by ameliorating orthostatic hypotension.…”
Section: Epidural Stimulationmentioning
confidence: 99%
“…LT benefits regarding autonomic functions have not been well characterized. For this reason, we implement our training paradigm with a focus on autonomic outcome measures, using four distinct groups that include two non-trained controls and a metabolic/exercise nonweight bearing group alongside an LT group that mimics the timing, session duration, manual assistance and weight support that are used in clinical studies 19,21,22,23,24 .…”
Section: Introductionmentioning
confidence: 99%